2012
DOI: 10.1002/ase.1274
|View full text |Cite
|
Sign up to set email alerts
|

The effects of passive and active learning on student preference and performance in an undergraduate basic science course

Abstract: Active learning is based on self-directed and autonomous teaching methods, whereas passive learning is grounded in instructor taught lectures. An animal physiology course was studied over a two-year period (Year 1, n = 42 students; Year 2, n = 30 students) to determine the effects of student-led seminar (andragogical) and lecture (pedagogical) teaching methods on students' retention of information and performance. For each year of the study, the course was divided into two time periods. The first half was dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 41 publications
3
52
2
Order By: Relevance
“…Moreover, the positive attitude towards lecture materials supports the inclusion of auditory, and reading-writing sensory modalities as part of a multimodal approach to teaching (Minhas et al, 2012;Breckler et al, 2009). …”
Section: Lecture Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the positive attitude towards lecture materials supports the inclusion of auditory, and reading-writing sensory modalities as part of a multimodal approach to teaching (Minhas et al, 2012;Breckler et al, 2009). …”
Section: Lecture Materialsmentioning
confidence: 95%
“…The favorability of lectures is often overwhelming, with students often agreeing that they were more beneficial than self-directed learning (Davis et al, 2014). Despite the push for more active modes of learning, these responses have shown that more traditional modes of delivery cannot be entirely ignored when developing curricula in anatomy and physiology (Choi-Lundberg, Low, Patman, Turner, & Sinha, 2016;Minhas, Ghosh, & Swanzy, 2012). Furthermore, it should be acknowledged that no singular approach (lectures, dissection/prosection, models, technology or living anatomy) fulfills all teaching objectives, thus a multimodal approach is best (Kerby et al, 2011).…”
Section: Traditional Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Active learning has been shown to be very effective in teaching college and medical students complex scientific and medical information (King 1993, Leonard 2000, Minhas et al 2012). Significant changes have occurred within anatomical education at the medical school level, including the movement away from stand-alone anatomy lecture and lab towards problem-and/or team-based approaches where anatomy is part of a multidisciplinary learning experience (Drake 2014, Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From the student perspective, CATE provides both active and passive learning opportunities 1 Usage is self-directed to provide flexibility and is driven by a student's needs. 2,3 CATE can help reinforce lecture material and provides many practice problems.…”
Section: Goalsmentioning
confidence: 99%